2019
DOI: 10.11591/ijece.v9i1.pp163-169
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage roll-off for sub-10 nm asymmetric double gate MOSFET

Abstract: Threshold voltage roll-off is analyzed for sub-10 nm asymmetric double gate (DG) MOSFET. Even asymmetric DGMOSFET will increase threshold voltage roll-off in sub-10 nm channel length because of short channel effects due to the increase of tunneling current, and this is an obstacle against the miniaturization of asymmetric DGMOSFET. Since asymmetric DGMOSFET can be produced differently in top and bottom oxide thickness, top and bottom oxide thicknesses will affect the threshold voltage roll-off. To analyze this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The maximum value of the total leakage current is dominated by the subthreshold leakage and equals to 54.102×10 -9 A. More details and more references related to the nanoscale transistor could be found in [22][23][24][25].…”
Section: Band-to-band Tunneling Leakage Current Comparisons and Simulmentioning
confidence: 99%
“…The maximum value of the total leakage current is dominated by the subthreshold leakage and equals to 54.102×10 -9 A. More details and more references related to the nanoscale transistor could be found in [22][23][24][25].…”
Section: Band-to-band Tunneling Leakage Current Comparisons and Simulmentioning
confidence: 99%
“…Other technological parameters were investigated in our other research paper [26] where we have reported that the base width W b has an important impact on the static current gain β because when we reduce it, the static current gain increases in an important way, while for the emitter length L e when we increase it the static current gain increases slightly. The reduction of transistor size has many advantages in different aspects especially in the technological one, among these advantages we cite the increase of operation speed and improvement of the device reliability by low power consumption, and smaller devices are required for various reasons, for that manufacturers are fabricating them in accelerating way, by example ultrafine transistors are intended for applications such as semiconductor integrated circuits [27,28]. The base layer of the SHBT is the most important and critical layer of this device, because technological parameters related to the base layer such as the width and the doping concentration have an important impact on the static current gain β in comparison to other investigated parameters such as the emitter length and the collector doping concentration.…”
Section: Output Electrical Characteristicsmentioning
confidence: 99%
“…The main obstacle of shrinking the dimension of MOSFET is the decrease in gate controllability over the channel due to high electric field [1][2][3][4]. An alternative solution to improve the gate control over the channel is by adding an extra gate [5][6][7][8][9][10]. Multi-gate MOSFETs have been recognized promising candidates for future scaling of MOSFET technologies.…”
Section: Introductionmentioning
confidence: 99%